Community-linked maternal death review (CLMDR) to measure and prevent maternal mortality: a pilot study in rural Malawi. Issue 4 (20th April 2015) - Bayley, Olivia; Chapota, Hilda; Kainja, Esther; Phiri, Tambosi; Gondwe, Chelmsford; King, Carina; Nambiar, Bejoy; Mwansambo, Charles; Kazembe, Peter; Costello, Anthony; Rosato, Mikey; Colbourn, Tim
Abstract : Background: In Malawi, maternal mortality remains high. Existing maternal death reviews fail to adequately review most deaths, or capture those that occur outside the health system. We assessed the value of community involvement to improve capture and response to community maternal deaths. Methods: We designed and piloted a community-linked maternal death review (CLMDR) process in Mchinji District, Malawi, which partnered community and health facility stakeholders to identify and review maternal deaths and generate actions to prevent future deaths. The CLMDR process involved five stages: community verbal autopsy, community and facility review meetings, a public meeting and bimonthly reviews involving both community and facility representatives. Results: The CLMDR process was found to be comparable to a previous research-driven surveillance system at identifying deaths in Mchinji District (population 456 500 in 2008). 52 maternal deaths were identified between July 2011 and June 2012, 27 (52%) of which would not have been identified without community involvement. Based on district estimates of population (500 000) and crude birth rate (35 births per 1000 population), the maternal mortality ratio was around 300 maternal deaths per 100 000 live births. Of the 41 cases that started the CLMDR process, 28 (68%) completed all five stages. We found the CLMDR process to increase the quantity of information available and to involve a wider range of stakeholders in maternal death review (MDR). The process resulted in high rates of completion of community-planned actions (82%), and district hospital (67%) and health centre (65%) actions to prevent maternal deaths. Conclusions: CLMDR is an important addition to the established forms of MDR. It shows potential as a maternal death surveillance system, and may be applicable to similar contexts with high maternal mortality.